A2.35 Glatiramer acetate restores the defective activity of regulatory B cells in SLE. (24th February 2016) - Amrouche, K; Pers, JO; Hillion, S; Jamin, C
Abstract : Background and objectives: Glatiramer Acetate (GA) is a synthetic pol ypeptide used in treatments of multiple sclerosis. Numerous studies have been performed to understand its effects on immune cells, but its role on B cells has been hardly described. Treatment of experimental autoimmune encephalomyelitis mice with GA has been shown to increase the frequency of CD5 + CD1dHigh B cells known to develop regulatory function. The possibility therefore exists that GA might activate regulatory B (Breg) cells. The aim of our work was to evaluate the ability of GA to stimulate the regulatory functions of B cells in healthy individuals and to appraise its effect on SLE Breg cells known to be defective. Materials and methods: B cells were purified from SLE and healthy donors and stimulated for 4 h with GA. Autologous T cells were stimulated with anti-CD3 and anti-CD28 Abs. Their proliferation was evaluated by flow cytometry and the concomitant production of IFNgamma evaluated by ELISA. The regulatory activities of B cells on T cell responses were evaluated after 4 days in co-culture experiments. Phenotypical analyses by flow cytometry were performed using FITC-conjugated GA to identify the subsets of B cells able to catch the GA. Results: The proliferative response and the IFNgamma production of T cells from healthy donors were significantly decreased in the presence of GA-stimulated B cells compared to non-stimulated B cells. Interestingly, the defective regulatory activity of non-stimulated SLE B cells on SLE T cells was restored after 4-hour stimulation with GA before co-cultures. Memory B cells bound high level of FITC-conjugated GA in contrast to naïve B cells. After sorting and stimulation with GA, increased-GA dependent regulatory activities were specifically triggered in memory B cells and not naïve B cells. Conclusions: GA up-regulates the regulatory functions of B cells. These effects are mainly directed to the memory B cell pool. Specifically in SLE patients in which the Breg cells are defective and the memory B cell compartment abnormally elevated, our results suggest that GA treatment could restore the regulatory activity of the B cells and contribute to the efficacy of the GA-based therapeutics in autoimmune diseases.